Monetary policy and the flow of funds in the euro area - Riccardo Bonci (European Central Bank (ECB), 2011)
This paper provides new evidence on the transmission of monetary policy in the euro area, assessing the impact of an unexpected increase of the short-term interest on the lending and borrowing activity of the different economic sectors. We exploit the information content of the flow-of-funds statistics, that provide the most appropriate framework to analyse the flowing of funds from one sector (the lender) to the other (the borrower). We proceed in two steps. First, we estimate a small VAR model for the euro area over the period 1991Q1 to 2009Q2. Then, we extend the benchmark VAR model in order to include the flow-of-funds series and analyse the response of the latter variables to a contractionary monetary policy shock. We find that the policy tightening is followed by a worsening of the budget deficit; firms cut on their demand for bank loans, partially replacing them with inter-company loans, and draw on their liquidity to try to offset the fall of revenues associated with the slowdown of economic activity; households reduce net borrowing and increase precautionary saving in the short run. Consistent with the bank lending channel of monetary policy at work, the interest rate hike is followed by a short-run deceleration of credit growth, mainly driven by the response of banks.
Keywords: E32; E4; E52; G11; 330; credit growth; flow of funds; monetary policy